Prevalence and correlates of community re-entry challenges faced by HIV-infected male prisoners in Malaysia - Choi, P.; Desai, M. M.; Kavasery, R.; Govindasamy, S.; Kamarulzaman, Adeeba; Altice, Frederick L. (SAGE Publications, 2010)
HIV-infected prisoners face an inordinate number of community re-entry challenges. In 2007, 102 HIV-infected prisoners in Malaysia were surveyed anonymously within six months prior to release to assess the prevalence and correlates of community re-entry challenges. Staying out of prison (60.8%), remaining off drugs (39.2%), finding employment (35.3%) and obtaining HIV care (32.4%) were the re-entry challenges reported most frequently. Global stigma, negative self-image and public attitudes-related stigma were independently associated with challenges to obtaining HIV care. In multivariate analyses, those with previous incarcerations (adjusted odds ratio [AOR], 3.2; 95% confidence interval [CI], 1.4–7.6), higher HIV-related symptoms (AOR, 2.0; 95% CI, 1.0–4.1) and higher public attitudes-related stigma (AOR, 2.5; 95% CI, 1.2–5.1) had a significantly higher likelihood of identifying more re-entry challenges. Targeted interventions, such as effective drug treatment, HIV care and public awareness campaigns, are crucial for stemming the HIV epidemic and improving health outcomes among HIV-infected prisoners in Malaysia.